Primitive art in the Archipelago: Meaning and Continuity in the History of Indonesian Fine Art - Iswahyudi Iswahyudi (Randwick International of Social Science Journal, 2023)
The discussion about Indonesian art in this paper is deliberately limited to modern art. It seems appropriate that the name Nusantara is more popular with art in Indonesia which is still in the categories of primitive, classical and traditional art. A little bit about primitive art, which is easy to understand, is that works of art which, in terms of technique, materials and symbolic meaning, are still categorized as simple in nature. Usually primitive art is identified during the prehistoric period and relates to the early period of human culture, but if all artifacts are from the mesolithic or middle rock period or neolithic or new rock. Then, with regard to classical art, it could be said that the rise of this type of art occurred after entering the historical period or when life had settled down and there was already a regulated community through the institutions it created. Judging from the word classic etymologically means it has received a Nobel title. Such a non-lexical meaning is conventional, usually classical art is a work of art that has experienced its peak of beauty. So what can be said is that classical art is also a paradigmatic system of values that is widely adhered to by its supporters, so that works of art are usually always produced in palaces and are constantly celebrated, especially in terms of their perfection.